Fertilizing seedlings Cabralea canjerana (Vell.) Mart. (Canjerana) with slow-release fertilizer (Revista de Ciências Agroveterinárias, 2014)
The successful production of native seedlings in forest nurseries is in essence often limited by lack of information on the nutritional demands of the species. The substrate is not always able to provide all the nutrients that plants need for their better development, making it necessary to add fertilizer. A fertilization technique is the use of slow release fertilizers that may have advantages over conventional fertilizers. This study aimed to evaluate the development of Canjarana tree seedlings under doses of slow-release fertilizer. The experimental design was completely randomized with four sets of treatment in four replicates, with 40 plants as experimental units. The treatments were: T1 - 0 kg (control), T2 - 2 kg, T3 - 4 kg, T4 - 6 kg, T5 - 8 kg and T6 - 10 kg per m³ FLL substrate base. After 220 days following parameters were evaluated: total plant height, stem diameter, fresh shoot biomass, dry shoot biomass, root dry weight and total dry biomass, and calculated the maximum level of technical effi ciency. It was observed that in doses ranging from 6.22 to 9.86 kg m-3 we found that the largest development of the seedlings.
Keywords: Seedling quality; Nutrition; Cultivation of seedlings.